Identifying drug-microbiome interactions: the inactivation of doxorubicin by the gut bacterium Raoultella planticola - Yan, Austin (My University, 2015)
The human gut microbiota contributes to host metabolic processes. Diverse microbial metabolic enzymes can affect therapeutic agents, resulting in chemical modifications that alter drug efficacy and toxicology. These interactions may result in ineffective treatments and dose-limiting side effects, as shown by bacterial modifications of the cardiac drug digoxin and chemotherapy drug irinotecan, respectively. Yet, few drug-microbiome interactions have been characterized. Here, a platform is developed to screen for drug-microbiome interactions, validated by the isolation of a gut bacterium capable of inactivating the antineoplastic drug doxorubicin. Two hundred gut strains isolated from a healthy patient fecal sample were cultured in the presence of antibiotic and antineoplastic drugs to enrich for resistance and possible inactivation. Raoultella planticola was identified for its ability to inactivate doxorubicin anaerobically through whole cell and crude lysate assays. This activity was also observed in other Enterobacteriaceae and resulted in doxorubicin inactivation by the removal of its daunosamine sugar, likely mediated by a molybdopterin-dependent enzyme. Other potential drug-microbiome interactions were identified in this screen and can be analyzed further. This platform enables the identification of drug-microbiome interactions that can be used to study drug pharmacology, improve the efficacy of therapeutic treatments, and advance personalized medicine.
Keywords: microbiota; microbiome; personalized medicine; pharmacology; drug interactions; drug inactivation; resistance; doxorubicin; Raoultella; Raoultella planticola; pharmacokinetics; pharmacomicrobiomics